Introduction to bryophytes - Vanderpoorten, Alain ca. 20./21. Jh; Goffinet, Bernard 1966- (Cambridge University Press, 2009)
Bryophytes were a pivotal step in land plant evolution, and their significance in the regulation of ecosystems and the conservation of biodiversity is becoming increasingly acknowledged. This introductory textbook assumes no prior knowledge of bryophyte biology, making it ideal for advanced undergraduate and graduate students, as well as amateur botanists. The authors expertly summarise the diversity of bryophytes and outline recent advances in our understanding of their evolutionary history, their ecological roles and preferences, their distribution patterns and conservation needs. The text is highly illustrated throughout, with boxed summaries of topics of current relevance in bryophyte biology, and a glossary of technical terms
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Bryophytes; Moose